First One Hundred Corrective Surgeries for Tetralogy of Fallots: Lessons Learned (Medical Forum Monthly, 2021)
Objective: Tetrology of fallots(TOF) is the most common cyanotic heart disease with the incidence of 0.34/1000 live births. Results of surgery has tremendously improved in last two decades. In this article author is discussing the lessons that were learned while doing first one hundred primary repairs in the patients of tetrology of fallotsStudy Design: A Retrospective StudyPlace and Duration of Study: This study was conducted at the Children’s hospital Lahore, University of Lahore teaching hospital and Hameed Latif hospital Lahore from September, 2017 to February, 2020.Materials and Methods: Age, weight, pre-operative status, intra operative time, management strategies, icu stay, hospital stay and follow up echocardiogram were looked for. Mortality and complications were given in percentages.Results: 100 primary repairs were done, mortality rate was 9%. Complete heart block occurred in 1, JET in 10, mean icu stay was 40hrs, mean ventilation time was 12 hours, mean duration of inotropes was 30 hours.Conclusion: Pre-operative MAPCA coiling, adequate right ventricular outflow tract resection, avoidance of pulmonary regurgitation, and good post-operative care can produce acceptable results after repair of tetralogy of fallots.